Hesitant Fuzzy Evaluation of System Requirements in Job Matching Platform Design - Onar, Sezi Çevik; Öztaysi, Basar; Kahraman, Cengiz (Springer International Publishing, 2017)
System requirements are vital for software development. Defining the appropriate requirements and their importance levels and taking the necessary actions to fulfill the most crucial ones are the keys to a successful software program. However, prioritization of the requirements is a complex problem that involves fuzziness and ambiguities. In this study, we propose a multi-criteria decision-making approach based on HFLTS (Hesitant Fuzzy Linguistic Term Sets) to evaluate the system requirements. The proposed method is applied to G@together project that focuses on developing an electronic job-matching platform for disadvantaged people.